Students' Perceptions Of The English Club Extracurricular Program In Terms Of Improving Motivation To Learn English - Bauty, Juwita Melinda; Handayani, Rita; Surveyanie2, Rinna Fitry; Vania, Talitha Rahma; Wati, Helmalia; Marhamah, Zumrotul (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2023)
The purpose of this study is to discover what characteristics drive students to learn English and their English learning success in the participant at an English club. A questionnaire was used to collect data to assess the percentage of elements in English language acquisition based on current theories. A sample of 20 students was chosen at random to evaluate and measure the students' motivation and English learning achievement. In this study, a collection of 10 questionnaires was employed to examine the relationship between many factors. Data analysis uses descriptive percentage analysis for questionnaires, while for interviews and observations the data is reduced and presented. The research results show that students who take part in the extracurricular English Club feel more motivated to learn English.